“New Frontiers in the Search for Dark Matter” - AAVV, AAVV (Il Colle di Galileo, 2021)
The workshop brought together world experts working on the origin of dark matter, one of the most urgent questions in fundamental physics. For seven weeks, scientists explored new theoretical avenues as well as novel detection strategies. The event benefited from the presence of Simons Fellows, who led discussions on well-motivated theories and the status of current fast-moving experimental searches.